The Influence of Entrepreneurial Competence and Entrepreneurial Knowledge on Business Success in Msmes in Madiun City - Mustika Apriyani; Kustini Kustini (Jurnal Syntax Admiration, 2023)
The economic sector is a sector that is currently growing rapidly. Many business people have built their own businesses, both formal and informal businesses, one of which is MSMEs which play a role in increasing the country's income in the form of foreign exchange. East Java is a province with a growing economic performance that is superior to other provinces on the island of Java. Madiun City is also a developing city in the East Java region so that the development of MSMEs in Madiun City from year to year is sure to experience rapid growth. This study aims to analyze the influence of Entrepreneurial Competence and Entrepreneurship Knowledge on Business Success in MSMEs in Madiun City. The subjects in this study were business actors in the food and beverage business in Madiun City, totaling 30 business actors and using 30 samples determined by the saturated sampling method. This research uses quantitative methods with SEM-PLS (Structural Equation Model – Partial Least Square) analysis techniques. This study concludes that the results of hypothesis testing show a significant and positive effect between entrepreneurial competence and entrepreneurial knowledge on business success. This means that the entrepreneurial competency level of MSME actors regarding business success is getting better so that they can manage their potential into opportunities and can be developed in the future.